Analisis Infrastruktur Teknologi Informasi Pada Sekretariat DPRD Provinsi Sumatera Selatan - Septiano K, M. Calvin; Maisito, Eka; Purwani, Fenny (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study analyzes the information technology (IT) infrastructure at the Secretariat of the Regional Peoples Representative Council (DPRD) of South Sumatra Province to assess its readiness in supporting legislative functions and public services. Using a qualitative case study approach, the research evaluates seven IT infrastructure components: hardware, software, networks, data centers, cloud services, security systems, and IT service management. Data were collected through semi-structured interviews, field observations, and document analysis (performance reports, IT SOPs, and SPBE documents). SWOT analysis identified strengths such as adequate hardware and SPBE compliance, weaknesses including limited data center redundancy and low public bandwidth, opportunities from national SPBE policies, and threats such as cyberattacks and regulatory changes. Gap analysis highlighted discrepancies between current infrastructure and target benchmarks, such as the need for Tier-3 data centers and 300 Mbps public bandwidth. The study proposes a 20252029 strategic roadmap focusing on hybrid cloud adoption, ITIL/COBIT-based governance, and digitalization of archival systems. Findings emphasize the urgency of aligning IT infrastructure with national e-Government standards to enhance transparency, public satisfaction, and disaster resilience. Recommendations include budget reallocation, workforce upskilling, and integrating e-Budgeting with e-Governance platforms.